(Re)defining Entrepreneurship in a Post-pandemic Context (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
The theme of entrepreneurship in the post-pandemic context is essential for the economic and social revitalization of economies. Despite this importance, this theme has hardly been explored, and therefore one of the central aspects of this reprint is to bring the debate on the competitiveness of micro-, small-, and medium-sized enterprises in various sectors to academic discussion. Through 11 chapters, involving the collaboration of more than 30 authors, this reprint pragmatically discusses a wide range of strategies and critical success factors for fostering entrepreneurship. This reprint also presents a set of practical solutions for various sectors, from tourism to agriculture, covering several countries, from Latin America to Asia to Europe. The various chapters present very diverse methodological approaches.